Friends and allies: LGBT+ inclusion in statistics and data science. Issue 3 (29th May 2019) - Thornton, Suzanne; Green, Brittany; Benn, Emma
Abstract : At a conference last year, Suzanne Thornton, Brittany Green andEmma Benn organised a panel session to share advice and recommendations for making the statistics and data science community more inclusive and supportive of gender non‐conforming and LGBTQ persons. Here they summarise their discussion in the hope of continuing the conversation Abstract : At a conference last year, Suzanne Thornton, Brittany Green and Emma Benn organised a panel session to share advice and recommendations for making the statistics and data science community more inclusive and supportive of gender non‐conforming and LGBTQ persons. Here they summarise their discussion in the hope of continuing the conversation.